2014
DOI: 10.5897/jgrp2014.0439
|View full text |Cite
|
Sign up to set email alerts
|

Socio-economic effect of gully erosion on land use in Gombe Metropolis, Gombe State, Nigeria

Abstract: Gully erosion is one of the severe environmental problems facing Gombe metropolis. It threatens urban infrastructure, properties, lives and the physical growth of the town. This article assesses the socioeconomic effect of gully erosion in Gombe metropolis. The aim of the study was to assess the socioeconomic effect of gully erosion on land use in Gombe metropolis. Data used in this study were derived from field administration of questionnaire and focus group discussion. Three sampled gully profiles cutting ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…This result also conceived with the findings of [29], reported that in 2003, 3340 km 2 of deposited farmland soils (DFs) had been formed on the Loess Plateau of China (CLP), on which 1.67 billion kg crop yield per year was produce and the area of DFs and crop yield are expected to have doubled by 2020. The loss of land for cultivation is a serious social and economic consequence of soil erosion, given a situation where farming is the main occupation of majority of the people [4].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This result also conceived with the findings of [29], reported that in 2003, 3340 km 2 of deposited farmland soils (DFs) had been formed on the Loess Plateau of China (CLP), on which 1.67 billion kg crop yield per year was produce and the area of DFs and crop yield are expected to have doubled by 2020. The loss of land for cultivation is a serious social and economic consequence of soil erosion, given a situation where farming is the main occupation of majority of the people [4].…”
Section: Resultsmentioning
confidence: 99%
“…Pei Z., [29].The loss of soil fertility leads to steady decrease in crop yields and this make difficulties on the concern of the local farmers over their economic wellbeing [4]. At Garage farmlands Clay loam texture soils having a platy structure with soil pH (6.23), EC (0.012 dSm -1 ) organic matter (1.98%) having water holding capacity of (35%) with slow to moderate permeability were identified as depositional prosperities which relatively favors the production of rice as alluvial soils deposition.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These erosions result in the formation of gullies which significantly degrade the landscape of the region. Deforestation is also a contributing factor to erosion in the region, as trees that would otherwise be able to withstand erosion are cut down, leaving the soil exposed to erosion (Danladi & Ray, 2014).…”
Section: Introductionmentioning
confidence: 99%